Democratic teaching learning practices: A research perspective - Arnnapurna Dash; Sudarshan Mishra (Indonesian Journal of Education and Pedagogy, 2026)
The present paper is based on a review of the literature related to democratic teaching and learning practices. It delves into the relationship between the social, cultural and political influences on education and the impact of education on society. Education is shaped by social life, like family, community and the state. Culture influences education by passing traditions, language and values through schools; state controls education through policies, laws, and funding, deciding what and how students learn. In return, education shapes society by improving knowledge, skills, and awareness among people. It helps people to take part in political decision and also brings social change. Emphasising democracy as a universally respected system, it emphasises the importance of raising awareness and understanding of democratic principles, especially in educational settings. The paper reviews educational theories that advocate for the promotion of democratic values ​​and active participation in democratic processes in schools. Furthermore, the paper emphasises the role of schools in promoting democratic ideals such as equality, freedom, and political participation, thus making individuals responsible citizens. The paper highlighted significant gaps in the existing literature, offering avenues for future research. These gaps include the need for research examining the long-term impact of democratic education, the challenge of implementation, teacher preparation to effectively promote democratic practices, seeking diversity and inclusion in democratic classrooms, and student perspectives on democratic education. Furthermore, comparative research is needed on the different contextual factors that affect the effectiveness of democratic teaching and learning practices.